Gas exchanges, δ13C/12C isotopic ratio and enzymatic activity in bell pepper under different irrigation sheets - Ruiz-Machuca, Luz Maria; Broetto, Fernando [UNESP]; de-Souza, Mara Lucia Cruz [UNESP]; Santos-Coscolin, Renata Bruna dos [UNESP]; Costa, Vladimir Eliodoro [UNESP]; Garcia-Carrillo, Mario; Concilco-Alberto, Ernesto (Univ Sonora, 2024)
The cultivation of bell pepper demand irrigation practices to guarantee fruit production and quality. The objective of this work was to assess the physiological and biochemical changes, as well as the variation in isotopic discrimination of delta 13C 13 C in bell pepper plants submitted to different irrigation sheets. The experimental design was organized in a completely randomized design (CRD) with three treatments (irrigation sheets) and five replicas, sheet 1 (S1): Psi m m = 10 to 15 kPa, sheet 2 (S2): Psi m m = 34 to 40 kPa and sheet 3 (S3): Psi m m = 54 to 60 kPa. Four evaluations were performed at 50, 65, 80 and 95 days after transplantation (DAT), measuring Leaf water potential (Psi lw), lw ), net CO(2 )assimilation (A), A ), stomatal conductance (gs), gs ), transpiration (E), E ), isotopic discrimination (delta C-13/C-12), C-13/ C-12), enzyme activity of nitrate reductase (NR), superoxide dismutase (SOD) and catalase (CAT). Finally, fruits were collected to determine productivity. Bell pepper plants with less water availability and depending on their development, the leaf water potential was more negative, resulting in greater stomatal closure which caused a considerable decrease in the net CO(2 )assimilation, transpiration, enzyme activity of nitrate reductase and fruit production, and greater activity of antioxidant enzymes. The increase and duration of water restriction in bell pepper plants induced less isotopic discrimination of delta C-13.
Keywords: Capsicum annuum L.; carbon assimilation; hydric stress; metabolism productivity